PENGARUH PEMANENAN HASIL HUTAN TERHADAP TINGKAT KERUSAKAN. TEGAKAN TINGGAL PADA DUA HAK PENGUSAHAAN HUTAN (HPH) DI KALIMANTAN BARAT (The effect of logging to residual stand damages in two forest concessions in West Kalimantan) - Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Disturbed soil and vegetation caused by logging operation is difficult to be avoided, even in good logging operation.Past studies related to this problem. shows that forest concessions in Sumatera and Kalimantan used Indonesia Selective Cutting System (TPTI) as a basic activity in logging operation. However, because of the weakness of goverment control activity, most of the companies were looking for financial benefit only and neglect the sustainability of the forest.The aim of this study is to assess the number of commercial trees (diameter 20 m and up) damaged during logging operation.The study was carried out in two forest concessions: PT. Batasan/A and PT. Tanjungpura Bhakti/B in West Kalimantan,The results shows that :1. The average percentage of commercial trees damaged of diameter 20. cm and up during logging operation are 4. 6 % in A concession and 5. 6 % in B concession.2. The average number of trees in concession A are 8. 9 trees/ha while in concession B is 7. 8 trees/ha.